Meso-to-microscale fracture porosity in tight limestones, results of an integrated field and laboratory study. (May 2019) - Panza, E.; Agosta, F.; Rustichelli, A.; Vinciguerra, S.C.; Ougier-Simonin, A.; Dobbs, M.; Prosser, G.
Abstract: The complex fluid saturation distribution and influence of microscale and mesoscale fractures on the fluid accumulation and flow properties of carbonates are still interesting challenges for petroleum geologists. For this reason, in order to know the relative role played by the aforementioned features on the storage and migration properties of tight limestones, the present work focuses on a surface analogue cropping out in southern Italy. By first applying a deterministic Discrete Fracture Network (DFN) modelling to a 1 m 3 geocellular volume, an amount of 0.3% of fracture porosity and a fracture connectivity configuration above the percolation threshold are computed. In addition to mesoscale fracture porosity, in order to gather information on matrix porosity and microscale fractures, we investigate the pore type, geometry, and textural anisotropy of selected rock plugs by mean of integrated petrophysical, ultrasonic, and optical microscopy analyses experiments. Results show values of connected porosity ranging between 1% and 6%, presence of vugs localized along pre-existing structural heterogeneities, and the predominance of stiff pores within the carbonate matrix. The rare microfractures are mainly oriented orthogonal to bedding. The estimated crack density (0.19) shows that the contribution of fracture porosity at microscale (ɸ = 0.078%) is very low if compared to that of matrix porosity and also a structural configuration above the percolation. The present study therefore documents that the carbonate matrix forms an isotropic medium, which profoundly affects the storage capability of the study limestones. In fact, the amount of storage provided by carbonate matrix and microscale fractures is greater than that due to mesoscale fractures. Moreover, we document that the matrix contribution on porosity is much more significant than the contribution provided by microfractures. Finally, the present work shows the importance of integrating different methodologies on the assessment of fracture porosity at different scales of observation. In fact, a great benefit for development and production operations can be obtained by performing studies of surface analogs, which allow the detailed investigation of rock masses below seismic resolution. Highlights: The work focuses on the role played by micro and mesoscale fractures on the storage and migration properties of limestones. The mesoscale fracture porosity and connectivity are computed by using a deterministic DFN. The pore type, geometry, and textural anisotropy are investigated by mean of petrophysical and ultrasonic analyses. Results show the predominance of microscale matrix porosity over mesoscale fracture porosity.